ILLOCUTIONARY SPEECH ACTS ANALYSIS OF STUDENTS"™ CAPTION IN INSTAGRAM - Anggira, Ayu; Bunau, Eusabinus; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This researchs aims to investigate the use of illocutionary speech acts in students"™ caption in their Instagram account. In this research, the researcher used the theory of speech acts proposed by Searle (1976). The method of this research was a pragmatic study. Data was collected through a questionnaire and it was presented in a table. Furthermore, the subject in this research was sixth semester students of English Education Study Program in Universitas Tanjungpura. The research was done by observing and analyzing the students"™ caption in their Instagram. As a result, it can be concluded that there were three types of illocutionary speech acts used in the students"™ caption, they were expressive act (feeling), representative (assertion), and directive (suggestion). Then, the most frequently used in the caption was expressive act (to express their feeling) and the least frequently used was directive act (to give a suggestion).